Perceptions of the stressful job search for pediatric hematology/oncology fellows. Issue 4 (30th January 2023) - Nishitani, Miki; Moerdler, Scott; Kesselheim, Jennifer
Abstract: The pediatric hematology and oncology (PHO) workforce landscape has been evolving over the past decades, with concern for waning interest in the subspecialty. We aimed to evaluate the impact of the initial PHO job search on fellow stress and anxiety, in addition to perceptions of the job search experience and potential areas of improvement. An anonymous survey consisting of demographics, emotional health impacts such as stress and anxiety, and job search experiences was developed and distributed to program leadership at all 74 PHO fellowship programs. At least one representative from 49 (66%) programs responded. Faculty were less likely than fellows to perceive that fellows are struggling to find jobs ( p = .0198). However, faculty were more likely than fellows to perceive that fellows are either "extremely stressed" or "stressed" due to job search ( p = .0003). By June 2021, 30 of 44 (68%) candidates had been offered a position, and 80% of those had accepted. There were no significant associations between fellow stress level and job offering, proximity to their ideal goals, or change in career type. Common barriers to the job search included geographic constraints and partner employment. Respondents identified centralized job listings, formal training on career development strategies, introduction to various career paths, and more transparency about the search as needed interventions. The perception of difficulty and stress regarding the job search is endorsed by most, identifying a need for more interventions to improve the experience. These data also highlight unmet mentorship and educational needs among PHO fellows in preparing for the job search.